Isozyme variability among isolates of Ascochyta rabiei - and NEENA MIITER, G. UMA DEVI, MAHENDRA PAL (Indian Phytopathology, 2002)
Positive activity was observed for 7 out of 12 isozymes tested in native polyacrylamide gel electrophoresis (PAGE) for five isolates of Ascochyta rabiei viz., 011, G2, GL 866, ICH and ICK differing in pathogenicity. Esterase, malate dehydrogenase, acid phosphatase and catalase gave a polymorphic banding pattern whereas peroxidase, alkaline phosphatase and glutamate dehydrogenase resulted in monomorphic banding pattern. Identical protein profile for all the isolates with respect to major bands and differences in the minor bands were observed in SOS-PAGE for total proteins. UPGMA method of cluster analysis grouped these isolates into two new clusters with 011 and G2 in one cluster and GL 866, ICH and ICK in the other cluster. In the second cluster, isolate ICH was further separated from GL 866 and ICK.